Protective effects of Salvianic acid A against multiple-organ ischemia-reperfusion injury: a review - Yang, Shiyu; Chen, Heming; Su, Wei; Luo, Yunchun; Liao, Jun; Wang, Yun; Xiong, Liyan; Zhang, Chuan; Li, Fei; Chen, Zhe-Sheng; Wang, Tingfang (Frontiers in Pharmacology, 2023)
Ischemia-reperfusion (I/R) injury refers to a new injury caused by reperfusion after the restoration of ischemic tissue or organ blood supply. Salvianic acid A (danshensu) is a primary active ingredient extracted from Salvia miltiorrhiza. It has a protective function against I/R injury in the cardiovascular system, brain, liver, kidney, gastrointestinal tract, and other organs. This article reviews evidence of the protective effects of Salvianic acid A and its potential mechanisms of action in organ I/R injury protection. The aim of this review is to investigate the role of Salvianic acid A in the treatment of I/R injury, providing a reference resource that could facilitate subsequent studies. This is a provisional file, not the final typeset article I/R injury is a challenging and life-threatening clinical problem that contributes to the pathology of a wide range of conditions [7][8] . Previous studies have found that the underlying molecular mechanism of I/R injury involves various complex pathological processes, including complement system activation [9] , platelet-leukocyte aggregation [10][11] , increased free radical production [12] , calcium overload [13] , mitochondrial membrane potential destruction [14] , reactive oxygen species (ROS) formation [15] , endothelial dysfunction [16] , and endoplasmic reticulum stress [17][18] . Severe I/R injury can also cause cell death through the induction of necrosis, apoptosis, autophagy, and other pathways [19] . Although considerable progress has been made in recent years towards understanding the pathophysiology of I/R injury, safe and effective treatment methods are limited in clinical practice [20][21] . Therefore, it is imperative to explore new drugs to control and treat I/R injury.